Exploring photovoice-based educational games for building self-confidence in middle childhood children - Sisya Ayumi Nurzauza; Rosa Karnita (Deskomvis: Jurnal Ilmiah Desain Komunikasi Visual, Seni Rupa dan Media, 2025)
Self-confidence during middle childhood (ages 6–12) plays an essential role in children’s social, emotional, and academic development. At this stage, children begin to evaluate their abilities and form self-perceptions influenced by learning experiences and social interactions. However, limited opportunities for reflective and creative self-expression in elementary school settings may affect the development of children’s self-confidence. This condition highlights the urgency of exploring approaches that provide developmentally appropriate expressive spaces for children. This study aims to explore the potential of a photovoice-based approach as a conceptual foundation for designing educational games that support self-confidence development in elementary school children in Bandung. The research employed a descriptive qualitative method supported by literature review and questionnaire-based data collection. Primary data were obtained from 19 parents of children aged 6–12 years from public and private elementary schools in Bandung. The questionnaires explored children’s daily activities, confidence tendencies, and preferred modes of expression. As an adaptation of photovoice principles, children were encouraged, with parental guidance, to represent aspects of their self-identity and experiences through visual media. The findings indicate that children tend to express themselves more confidently through visual and creative media compared to purely verbal forms. While positive self-appreciation was observed, situational hesitation and self-doubt were also identified. These results suggest that a photovoice-based visual approach can serve as a relevant foundation for designing participatory educational games that foster self-confidence in elementary school children.